Electrical, structural, and autonomic atrial remodeling underlies atrial fibrillation in inflammatory atrial cardiomyopathy - Murakata, Yoshiko; Yamagami, Fumi; Murakoshi, Nobuyuki; Xu, DongZhu; Song, Zhonghu; Li, Siqi; Okabe, Yuta; Aonuma, Kazuhiro; Yuan, ZiXun; Mori, Haruka; Aonuma, Kazutaka; Tajiri, Kazuko; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There is growing evidence indicating a close relationship between inflammation and atrial fibrillation (AF). Although underlying inflammatory atrial cardiomyopathy may contribute to the development of AF, the arrhythmogenic remodeling caused by atrial inflammation has not been elucidated in detail. Herein, we examined electrical, structural, and autonomic changes in the atria in a mouse model of autoimmune myocarditis. Methods BALB/c mice were immunized with cardiac myosin peptide (MyHC-α614–629) conjugated with complete Freund’s adjuvant on days 0 and 7. Susceptibility to AF was assessed using right-atrial burst pacing. Results The mice immunized with MyHC-α614–629 showed an inflammatory atrial cardiomyopathy phenotype, with enlarged atria; a high degree of inflammatory cell infiltration primarily consisting of CD4+ T cells, CD8+ T cells, Ly6GlowCD11b+ macrophages, and CD11c+ dendritic cells; and severe interstitial fibrosis with collagen deposition. These mice demonstrated significantly enhanced susceptibility to AF, as indicated by their increased AF induction rate and duration. In addition, the expression of potassium channels (Kcnh2, Kcnd3, and Kcnj2) and calcium handling-associated genes (Cacna1c, Camk2, Ryr2, and Atp2a2) was downregulated. Connexin 40 expression was significantly downregulated, leading to frequent lateralization to the inflamed atrium. Sympathetic and parasympathetic innervation and neurotrophin expression (nerve growth factor and brain-derived neurotrophic factor) were upregulated in the inflamed atria. Conclusion Inflammatory atrial cardiomyopathy promotes susceptibility to AF via arrhythmogenic electrical, structural, and autonomic remodeling of the atria.